Closing the governance gap in joint ventures - Bamford, James D., 1965-; Walker, Geoff (MIT Sloan Management Review, 2022)
Joint ventures make meaningful contributions to corporate revenue and can enable new growth strategies, but they increase their shareholders' risk exposure, often in ways that are hard to manage. The authors see a clear statistical correlation between good governance and the medium-term financial and strategic performance of JVs. To build a foundation for good governance, JV owners must reach clarity and alignment on the JV's purpose and operating model.